Pengaruh ekstrak daun pepaya (Carica papaya linn) terhadap larvasida Aedes aegypti - Fajriansyah Fajriansyah; Ika Sartika (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Transmission of Dengue Hemorrhagic Fever (DHF) is strongly influenced by the presence of Aedes aegypti mosquito larvae. The most effective method for tackling DHF is by killing the presence of Aedes aegypti larvae. Reducing the negative impact of using chemical larvicides can be done through a safer alternative model, namely natural larvicides from plants. The plant studied with a characteristic ability to kill Aedes aegypti larvae is papaya leaves. Papaya leaf extract contains compounds of alkaloids, flavonoids, papain, saponins, tannins, and papain, which can kill Aedes aegypti larvae.Objective: This study aims to determine the effectiveness of papaya leaf extract (Carica papaya Linn) and the effect of concentration as Aedes aegypti larvicide.Method: The design used in this study was experimental, using 240 Aedes aegypti larvae, three treatments, and three repetitions. The research was carried out at the Laboratory of the Environmental Health Department of Aceh Health Polytechnic, Ministry of Health in 2021. The data was collected through observations every 1 hour for the first 3 hours. The analysis used was the One Way Anova statistical test and continued with the Least Significance Different (LSD) test at 95% CI.Results: The results showed that the average mortality of Aedes aegypti larvae was at a concentration of 10% (10), a concentration of 20% (13), and a concentration of 30% (16). The results of the Anova test showed that giving papaya leaf extract affected the mortality of Aedes aegypti larvae (p = 0.000). The most effective concentrations in killing Aedes aegypti larvae were 20% and 30%.Conclusion: Papaya leaf extract was very effective as a larvacide of Aedes aegypti, and it was found that concentrations of 20% and 30% were the best formulas for larvicides.